Electronic Structure Evolution with Composition Alteration of Rh(x)Cu(y) Alloy Nanoparticles - Palina, Natalia (Sci Rep, 2017)
The change in electronic structure of extremely small Rh(x)Cu(y) alloy nanoparticles (NPs) with composition variation was investigated by core-level (CL) and valence-band (VB) hard X-ray photoelectron spectroscopy. A combination of CL and VB spectra analyses confirmed that intermetallic charge transfer occurs between Rh and Cu. This is an important compensation mechanism that helps to explain the relationship between the catalytic activity and composition of Rh(x)Cu(y) alloy NPs. For monometallic Rh and Rh-rich alloy (Rh(0.77)Cu(0.23)) NPs, the formation of Rh surface oxide with a non-integer oxidation state (Rh((3−δ)+)) resulted in high catalytic activity. Conversely, for alloy NPs with comparable Rh:Cu ratio (Rh(0.53)Cu(0.47) and Rh(0.50)Cu(0.50)), the decreased fraction of catalytically active Rh((3−δ)+) oxide is compensated by charge transfer from Cu to Rh. As a result, ensuring negligible change in the catalytic activities of the NPs with comparable Rh:Cu ratio to those of Rh-rich and monometallic Rh NPs.